Safe Resection of Renal Cell Carcinoma with Liver Invasion Using Liver Hanging Technique Supported by Preoperative Portal Vein Embolization - Masato Fujii; Toshio Kamimura; Hiromasa Tsukino; Eiji Furukoji; Tatefumi Sakae; Koichi Yano; Naoya Imamura; Shoichiro Mukai; Atsushi Nanashima; Toshiyuki Kamoto (Case Reports in Urology)
In cases of RCC with liver involvement, partial hepatectomy is known to provide a better chance of survival for patients. For this reason, complete resection with clear surgical margin is thought to be necessary to achieve favorable outcome. Anterior liver hanging maneuver was extremely useful during hemihepatectomy in this rare type of RCC. A 63-year-old male was diagnosed with a large right renal cell carcinoma. The tumor measured 10 cm in diameter with tumor thrombus toward the inferior vena cava (IVC). In addition, we observed direct infiltration to the liver. We attempted a preoperative portal vein embolization (PVE) to preserve residual liver volume and function after right lobectomy. After PVE the resected volume decreased from 921 cm3 (71%) to 599 cm3 (53.4%). During the procedure, a nasogastric tube was placed in the retrohepatic space for liver hanging maneuver according to the original Belghiti’s maneuver after dissection of the renal artery and vein. After hepatic parenchymal transection exposing vena cava, the right hepatic veins were safely transected using vascular stapler; right nephrectomy and hemihepatectomy were performed. The patient recovered without postoperative hepatic or urinary complications and has remained free of local recurrence and any de novo metastasis for 18 months.